Service Orientation, Integrity and Commitment to Students; Administrative Performance Management in Madrasah - Gidayani, Gidayani; Kholid, Idham; Meriyati, Meriyati; Septuri, Septuri; Koderi, Koderi (JURNAL AL-TANZIM, 2022)
This study aims to understand service orientation, integrity, and commitment in the performance management system of the head of administration within the scope of students in Madrasah Aliyah Negeri in Lampung Province. This study uses a phenomenological qualitative approach, where the researcher uses interviews, observations, and documentation to obtain data. The data analysis refers to the interactive data analysis model from Milles & Huberman, namely data reduction, data presentation, conclusion drawing, and verification. The results showed that service orientation, integrity, and commitment in the administrative performance management system at Madrasah Aliyah Negeri Lampung Province were carried out in a planned and systematic way through various varied activities to be able to provide good service to students. This research has implications for improving the quality of administrative resources in providing optimal services to students and stakeholders.